2017
DOI: 10.1093/jtm/tax050
|View full text |Cite
|
Sign up to set email alerts
|

The quantified self during travel: mapping health in a prospective cohort of travellers

Abstract: Our study offers a revolutionary look at an almost real-time timeline of health events and behaviours during travel using mHealth technology. Non-infectious disease related health issues were common in this cohort, despite being largely unaddressed in traditional travel medicine research and suggest a substantial potential for improving evidence-based travel medicine advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…71,85,86 More research is needed to establish the most promising uses of these data for travel health, and the combination of information extracted from traditional and innovative data sources are beginning to be produced and yield a proof of concept and road map for future studies on individual's risk assessment in travel medicine. [43][44][45] For instance, phylogeographic analyses can relate travel and epidemiological dynamics by integrating mobile data with expanding genetic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71,85,86 More research is needed to establish the most promising uses of these data for travel health, and the combination of information extracted from traditional and innovative data sources are beginning to be produced and yield a proof of concept and road map for future studies on individual's risk assessment in travel medicine. [43][44][45] For instance, phylogeographic analyses can relate travel and epidemiological dynamics by integrating mobile data with expanding genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, prior research suggests that participants may be more likely to share sensitive or socially unacceptable information on an online form, improving understanding of rates of risky behaviours during travel. 72 Farnham et al [42][43][44][45] used mHealth technology to identify the range of health outcomes during travel using real-time monitoring and daily reporting of health behaviours and outcomes and identify traveller subgroups who may benefit from more targeted advice before and during travel. In this mHealth-based study, non-infectious disease-related health issues were commonly found in travellers, despite being largely unaddressed in traditional travel medicine research; in addition, clear patterns of traveller behaviour and health outcomes emerged, suggesting that subgroups of travellers exist for whom specialized medical advice is needed.…”
Section: Mhealth Applications and Risk Assessment In Travellersmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of accidents were reported by almost one quarter of the study participants. 6 A previous data extrapolation of a Swiss accident insurance company indicated that one Swiss citizen dies each month of a sports or traffic accident in Thailand. 7 Even if the exact number found in the insurance study might be overestimated, such estimations are shocking.…”
Section: Innovative Researchmentioning
confidence: 99%
“…Where the trend is clear, adjusting policy to ensure safety of all travellers including those who may be injured by chemoprophylaxis, as well as those at risk of malaria. Tracking the travellers itineraries could provide data to geographical exposure in countries with patchy endemicity and provide evidence to define high risk destinations (8). We are conscious with the very low rates now identified in S E Asia and S America, policy makers may be doing more harm when recommending chemoprophylaxis than preventing cases of P falciparum malaria.…”
mentioning
confidence: 99%